2010
DOI: 10.1017/s1751731110000558
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mannanoligosaccharides supplementation on caecal microbial activity of rabbits

Abstract: A total of 200 weaned (35 days) hybrid Hyla rabbits were randomly divided among five groups housed in bicellular cages (20 cages per group). Between 35 and 60 days of age, the groups were submitted to the following treatments: group ANT (positive control) fed a basal diet supplemented with antibiotics (colistin sulphate, 144 mg/kg; tylosin, 100 mg/kg; and oxytetracyclin, 1000 mg/kg); groups MOS_0.5, MOS_1.0 and MOS_1.5 fed the basal diet supplemented with 0.5, 1.0 and 1.5 g/kg mannanoligosaccharides (MOS), res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 21 publications
4
31
1
1
Order By: Relevance
“…This effect could be ascribed to the prebiotic effects of chitin that can increase the production of butyric volatile fatty acid in caeca (Khempaka et al, 2011;Bovera et al, 2016). Butyric acid is considered the prime enterocytes energy source (Bovera et al, 2010) and it is also necessary for the suitable development of the gut-associated lymphoid tissue (Mroz, 2005). It is documented that butyrate is the major intestinal energy source even when other fuel sources (glucose or glutamine) are available and could stimulate the growth of colorectal and ileal mucosal cells (Montagne et al, 2003;Topping and Clifton, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…This effect could be ascribed to the prebiotic effects of chitin that can increase the production of butyric volatile fatty acid in caeca (Khempaka et al, 2011;Bovera et al, 2016). Butyric acid is considered the prime enterocytes energy source (Bovera et al, 2010) and it is also necessary for the suitable development of the gut-associated lymphoid tissue (Mroz, 2005). It is documented that butyrate is the major intestinal energy source even when other fuel sources (glucose or glutamine) are available and could stimulate the growth of colorectal and ileal mucosal cells (Montagne et al, 2003;Topping and Clifton, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, MOS was reported to improve the performance and immunity of animals (Rosen 2007;Bovera et al 2010;Attia et al 2014a,b). The manner of action of MOS could be attributed to enhancing the nutrient digestibility, and improving gastrointestinal beneficial microbiota and the intestinal morphology (Hooge 2004;Hooge & Connolly 2011).…”
Section: Discussionmentioning
confidence: 99%
“…(2010a) found that, in comparison with antibiotics, the concentration of 1 g/kg of MOS induced an important reduction of mortality rate in rabbits under critical conditions involving an episode of Epizootic Rabbit Enteropathy. In vitro tests (Bovera et al., 2010b) also showed that MOS at 1.0 g/kg seems to have the best effect on microbial fermentations giving higher in vitro organic matter digestibility. However, in both studies, the conditions imposed by the farm made it impossible to use a control group fed without additives (antibiotics or mannan‐oligosaccharides).…”
Section: Introductionmentioning
confidence: 99%